Intravascular cryptococcal culture filtrate (CneF) and its major component, glucuronoxylomannan, are potent inhibitors of leukocyte accumulation. - Dong, Z M (1995)
Disseminated cryptococcosis is characterized by high titers of cryptococcal polysaccharides in serum and minimal cellular infiltrates in infected tissues of patients. The main objective of this study was to determine whether the circulating cryptococcal polysaccharides could contribute to the lack of cellular infiltration into infected tissues. To assess this possibility, a gelatin sponge implantation model was used. We found that intravenous (i.v.) injection of mice with cryptococcal culture filtrate antigen (CneF) inhibited migration of leukocytes (neutrophils, lymphocytes, and monocytes) into the intrasponge sites of acute inflammation induced by CneF, tumor necrosis factor alpha, or formylmethionyl leucyl phenylalanine. In addition, i.v. administration of CneF inhibited leukocyte migration into the intrasponge sites of a cell-mediated immune reaction irrespective of whether the delayed-type hypersensitivity response was to CneF or the mycobacterial antigen purified protein derivative. Glucuronoxylomannan, a major constituent of CneF and a major cryptococcal antigen detected in the sera of patients with disseminated cryptococcosis, when given i.v. to mice, inhibited leukocyte migration into the sponges. Our results suggest that the minimal cellular infiltrates observed in infected tissues of cryptococcosis patients may be due, in part, to the circulating cryptococcal polysaccharide functioning as we have demonstrated in the mouse model. Furthermore, the high titers of cryptococcal antigen in the sera of patients may diminish leukocyte migration in response to stimuli other than Cryptococcus neoformans, a point that may be relevant in AIDS patients with cryptococcosis.